2018
DOI: 10.1016/j.jtho.2017.11.135
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of Chemotherapy to Radiation Therapy Improves Survival in Elderly Patients with Stage III Non–Small Cell Lung Cancer

Abstract: We found that definitive chemoradiation resulted in a survival advantage compared with definitive radiation in elderly patients. Sequential chemotherapy and radiation was superior to concurrent chemoradiation. Although prospective trials are needed, this analysis suggests that chemoradiation should be strongly considered for elderly patients and the optimal sequencing of chemotherapy and radiation remains an unanswered question for this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 27 publications
1
62
0
Order By: Relevance
“…The OS results from this study are in-line with a published meta-analysis [22] and other recent population-based studies of patients diagnosed with unresected stage III NSCLC who received cCRT (median OS 13 to 18 months) [23][24][25], but are shorter than results for the standard radiation dose arm (29 months) in the recently completed Radiation Therapy Oncology Group (RTOG) clinical trial that evaluated optimal cCRT regimens (RTOG 0617) [26]. The current study did not assess radiation dose, and included patients not treated with radiation, or treated with radiation therapy only, all of which may explain discrepancies in findings between our study and RTOG 0617.…”
Section: Discussionsupporting
confidence: 87%
“…The OS results from this study are in-line with a published meta-analysis [22] and other recent population-based studies of patients diagnosed with unresected stage III NSCLC who received cCRT (median OS 13 to 18 months) [23][24][25], but are shorter than results for the standard radiation dose arm (29 months) in the recently completed Radiation Therapy Oncology Group (RTOG) clinical trial that evaluated optimal cCRT regimens (RTOG 0617) [26]. The current study did not assess radiation dose, and included patients not treated with radiation, or treated with radiation therapy only, all of which may explain discrepancies in findings between our study and RTOG 0617.…”
Section: Discussionsupporting
confidence: 87%
“…Treatment with chemoradiation was associated with improved OS versus that with radiation [hazard ratio (HR) = 0.66, 95% confidence interval (CI): 0.64-0.68, p <0.001]. Strikingly, when related to the concurrent chemoradiation, the sequential chemoradiation was associated with a 9% reduction in the risk for death (HR = 0.91, 95% CI: 0.85-0.96, p = 0.002) (31).…”
Section: Chemoradiotherapymentioning
confidence: 99%
“…1 Investigations indicate that the addition of chemotherapy to RT improves the efficiency of treatment in cancer patients. 2 There are serious efforts to improve and develop RT efficacy. 3 It is reported that the inhibition of certain signaling pathways is associated with the enhancement of RT response in several cancer types.…”
Section: Introductionmentioning
confidence: 99%